A comparison of clinical examination and ultrasound enthesitis indices in patients with psoriatic arthritis, adjusted for concomitant fibromyalgia. (March 2021) - Sapsford, Mark; Evans, Jobie; Clunie, Gavin; Jadon, Deepak
Objectives: To: (a) determine the extent of ultrasound (US)-detected peripheral enthesitis in a cohort of patients with psoriatic arthritis (PsA); (b) compare this with three clinical examination (CE) enthesitis indices; and (c) determine the effect of concurrent fibromyalgia on the evaluation of enthesitis. Methods: A prospective single-centre cross-sectional study of consecutive outpatients with established PsA undergoing clinical examination for enthesitis and US examination for inflammatory and structural lesions of enthesitis. Multivariable analyses tested for association between US scores, CE enthesitis indices and influence of concurrent fibromyalgia. Results: A total of 106 patients were assessed. Of these, 91/106 (85.8%) had CE enthesitis and 105/106 (99.1%) had ⩾1 US feature of enthesitis. There was a moderate correlation between US entheseal inflammation and both the Leeds Enthesitis Index (LEI) (Spearman rank, r  = 0.36) and Spondyloarthritis Research Consortium of Canada Enthesitis Index (SPARCC) ( r  = 0.44). US entheseal damage did not correlate with CE enthesitis indices. Twenty-eight (26.4%) patients were classified as having concurrent fibromyalgia, in whom multivariable regression analyses demonstrated no correlation between US scores and CE enthesitis indices. PsA patients without fibromyalgia demonstrated a statistically significant association between both LEI ( r  = 0.48, p  < 0.0001) and SPARCC ( r  = 0.62, p  < 0.0001) and US entheseal inflammation. Conclusion: There is a moderate association between US entheseal inflammation, but not damage, and CE enthesitis indices in patients with PsA. The presence of concurrent fibromyalgia is linked with higher CE enthesitis scores, without an increase in US inflammation, suggesting that CE enthesitis indices should be used/interpreted with caution in these patients. Imaging, including US, should be the preferred modality to detect enthesitis in PsA patients with concurrent fibromyalgia.